KAJIAN JURIDIS TERHADAP CORPORATE SOCIAL RESPONSIBILITY MENURUT HUKUM POSITIF INDONESIA (Solusi, 2023)
Corporate social responsibility is one of the important elements for every company to be able to maintain its existence in society. The issue of corporate social responsibility ia a very popular problem in foreign countries. But it is not the case in indonesia, in indonesia corporate social responsibility is something that is not yet knows among entrepreneurs. Even so, regulations regarding corporate social responsibility have been recognized by law although they are still very simple, namely investment laws, company laws, and environmental management laws.